IDENTIFIKASI MERKURI PADA BEBERAPA KRIM WAJAH YANG TERDAPAT DI PASAR BINJAI - Zuhairiah Zuhairiah; Siti Nurbaya; Yosy Cinthya Eriwaty Silalahi; Fitri Margaretta Simarmata (Jurnal Farmanesia, 2020)
Cosmetics are used to whiten the skin and also to avoid skin disorders both from inside and outside, such as blemishes, spots, freckles. The addition of mercury to cosmetics causes dark spots, allergies, irritation, and high doses can cause brain and kidney damage. Mercury is a substance that is prohibited by the Regulation of the Head of the Food and Drug Supervisory Agency (BPOM) of the Republic of Indonesia No. HK.00.05.42.1018 concerning cosmetics. The purpose of this study was to determine whether there was a mercury compound in facial whitening cream. The cream was taken at random from a whitening cream vendor in the Binjai market. Mercury identification was carried out at the Medan Regional Health Laboratory and from the results of research on 5 samples of facial whitening cream, it turned out that there was one sample containing mercury compounds, namely sample B, which did not meet the requirements.